Debt as power - Di Muzio, Tim; Robbins, Richard H. 1940- (Theory for a global age, 2016)
"Debt as power is a timely and innovative contribution to our understanding of one of the most prescient issues of our time: the explosion of debt across the global economy and related requirement of political leaders to pursue exponential growth to meet the demands of creditors and investors."